A Study of the Relationship Between Pigment Production and Biofilm Formation in Pseudomonas aeruginosa - Karim, Sally Abdul Aziz; Zwain, Luma Abdulhady; Mahmoud, Estabraq A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Eighty eight isolates of Pseudomonas aeruginosa were obtained from Central Child Teaching Hospital, Imamin Al-Kadhimin Medical City, Baghdad Teaching Hospital, National Center for Educational Laboratories, Imam Ali Hospital, Ibn Al-Baladi Hospital, as well as (38) clinical isolation obtained from previous studies and (22) environmental isolation obtained from previous studies and it was studied the effect of the type of cultural medium, temperature and different pH numbers in the production of pigments. The results showed that the isolates of Pseudomonas clinical (Pc18) and (Pc40) had the ability to form green pigments after 24 hours of incubation in the nutrient broth and after 72 hours in the heart infusion broth and Luria bertani broth after 72 hours, and they were yellowish-green in color. It was also noted that the isolate Pc18 showed the green pigment at a temperature of 25, 37, and 41°C after an incubation period of 72, 24, and 120 hours respectively, while the isolate Pc40 showed the yellowish green pigment at a temperature of 25°C after an incubation period of 72 hours, and it had a green pigment at a temperature of 37 and 41°C at a 24 and 120 hours incubation period. The results also showed the formation of a yellowish-green color after 72 hours of incubation of Pc18 isolate, while Pc40 isolate showed its ability to form green after 48 hours in the alkaline medium. In the acidic medium, the ability of Pseudomonas aeruginosa bacteria to form color during the incubation period of 120 hours was not observed. In the neutral medium, the results showed that the pigment for the two isolates was absorbed after 24 hours. The results of morphological detection showed biofilm formation by 11.11% was poorly formed, 88.89% was medium formation, and no strong isolates were observed. There was no effect of pigment formation on the ability of Pseudomonas aeruginosa to form biofilm